1970
DOI: 10.1111/j.1476-5381.1970.tb09564.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of halothane and catecholamines on heart rate and rhythm in the horse

Abstract: Summary1. Ventricular ectopic beats were recorded in eight of thirteen conscious horses following the intravenous administration of adrenaline in doses of 3 t4g/kg. Following pre-treatment with either atropine sulphate (0-1 mg/kg) or propranolol hydrochloride (0O1 mg/kg), the same dose level of adrenaline failed to produce ventricular ectopic beats. 2. Halothane anaesthesia sensitized the equine heart to the arrhythmogenic actions of adrenaline; the incidence and duration of ventricular arrhythmias being great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Although all three inhalants depress cardiorespiratory function in a dose-dependent manner, isoflurane and sevoflurane act similarly at equipotent concentrations, with both causing less depression of cardiac output and more depression of respiratory rate compared with halothane [10]. Halothane, unlike isoflurane and sevoflurane, has been reported to cause cardiac rhythm irregularities because of sensitization of the myocardium [64,65]. With the introduction of isoflurane, currently at a comparable cost, it is difficult to rationalize the continued use of halothane in the critically ill equine patient.…”
Section: Anesthetic Induction and Maintenancementioning
confidence: 99%
“…Although all three inhalants depress cardiorespiratory function in a dose-dependent manner, isoflurane and sevoflurane act similarly at equipotent concentrations, with both causing less depression of cardiac output and more depression of respiratory rate compared with halothane [10]. Halothane, unlike isoflurane and sevoflurane, has been reported to cause cardiac rhythm irregularities because of sensitization of the myocardium [64,65]. With the introduction of isoflurane, currently at a comparable cost, it is difficult to rationalize the continued use of halothane in the critically ill equine patient.…”
Section: Anesthetic Induction and Maintenancementioning
confidence: 99%
“…shown that the halothane has a potential role on the conducting tissues of the ventricle and even its increased sensitivity to catecholamine blood pressure alterations and arrhythmias resulted primarily from its action on these tissues 10 . Moreover, it has been confirmed that halothane caused a significant and dose-dependent decrease in cardiac output and this reduction was dependent to halothane effects on antipyrine disposition profoundly affected by this anesthetic agent 11 .…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated, the doseeffect curves obtained are parallel to each other. However, figure 2 illustrates the nonparallel nature of the dose-effect curve obtained with procaine amide in the Dose-effect curves obtained on the whole isolated cat heart preparation illustrating the diminution of heart rate produced by quinidine (13), l-atropine (20), d,l-atropine (13), d,l-homatropine (18), and l-scopolamine (9) (number of individual determinations in parentheses). same preparation in comparison to d,/-atropine and /scopolamine.…”
Section: Bradycardiamentioning
confidence: 99%